Content of Serious Illness Care conversation documentation is associated with goals of care orders—a quantitative evaluation in hospital - King, Seema; Douglas, Maureen; Javed, Sidra; Semenchuk, Jocelyn; Ghosh, Sunita; Dunne, Fiona; Moledina, Aliza; Fassbender, Konrad; Simon, Jessica (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background The Serious Illness Care Program (SICP) increases quality of documentation about patients’ values and priorities, but it is not known whether patient characteristics and goals of care are associated with the elements documented. The purpose of this study was to explore for associations between the quantity and type of elements documented after SICP conversations with patient characteristics and goals of care order. Methods Documentation of SICP conversations by internal medicine physicians with hospitalized patients was evaluated in a retrospective chart review between March 2018 to December 2019. The conversations occurred after SICP implementation in a Tertiary Hospital, Medical teaching unit which uses “Goals of Care Designation” (GCD) medical orders to communicate a patient’s general intent, specific interventions, and preferred locations of care. A validated SICP codebook was used to determine the frequency of conversation elements documented for (1) Goals and Values; (2) Prognosis/illness understanding; (3) End-of-life care planning and (4) GCD/Life-sustaining treatment preferences. Univariate and multivariate generalized linear models were used to analyze associations between quantity of elements documented and patient characteristics (age, gender, frailty, language spoken and GCD). Results Of 175 SICP conversations documented, in the univariate analysis more goals and values were documented for patients who understand/speak English (0.89; 95% CI: 0.14 - 1.63) and more content was recorded for patients with a non-resuscitative GCD focus (“Medical”: 2.42; 95% CI: 1.51 – 3.33; “Comfort”: 1.06; 95% CI: 0.24 – 1.88) although not in all domains. In the multivariate analysis, controlling for age, gender, language and frailty, the association between content scores and GCD remained highly significant. Patients with a non-resuscitative GCD had higher total domain scores than those with a resuscitative GCD (“Medical”: 1.27 95% CI: 0.42–2.13; “Comfort”: 2.67, 95% CI:1.71–3.62). Conclusion The type of content documented by physicians after a SICP conversation is associated with the patient’s goals of care.